From English as the medium to English as a medium: Perspectives of EMI students in Qatar. (July 2021) - Graham, Keith M.; Eslami, Zohreh R.; Hillman, Sara
Abstract: This study examined student attitudes toward the use of Arabic in English-medium instruction (EMI) in an international branch campus (IBC) in Qatar. A questionnaire was used to elicit attitudes of 57 engineering students (44 Arabic L1; 13 non-Arabic L1) taking EMI courses. Data were analyzed using descriptive statistics, a one-sample t -test, and a qualitative analytic deduction approach. Overall, findings showed that students generally welcomed Arabic in this IBC and were supportive of English as a medium of instruction rather than a monolingual conception of EMI. For non-Arabic L1 students specifically, data revealed that despite not speaking the language, the students held neutral views toward Arabic use in the IBC courses. Data on Arabic L1 student attitudes in various academic courses that compose the degree program showed that Arabic use was most favored in political science/history and least favored in math. The Arabic L1 students indicated positive attitudes toward the use of Arabic during class discussions but held neutral to negative attitudes toward its use in lectures, readings, and assignments. In light of the findings, policymakers, university administrators, and IBC instructors are encouraged to implement practices that align with English as a medium of instruction rather than a monolingual EMI.